How High-Arousal Language Shapes Micro- Versus Macro-Influencers’ Impact - Cascio Rizzo, Giovanni Luca; Villarroel Ordenes, Francisco; Pozharliev, Rumen; De Angelis, Matteo; Costabile, Michele (Journal of Marketing, 2024)
Influencer marketing is a popular strategy to connect with consumers. However, influencers’ use of overly high-arousal language in promoting products (e.g., “it's totally AMAZING!”) has raised questions about their true motivations. This article investigates how high-arousal language in micro- versus macro-influencers’ sponsored posts might shape engagement. A multimethod approach, combining automated text, image, video, and audio analyses of thousands of Instagram and TikTok posts with controlled experiments, demonstrates that high-arousal language increases engagement with micro-influencers, but it decreases engagement with macro-influencers, seemingly because it makes micro- (macro-) influencers appear more (less) trustworthy. Yet the negative effect of arousal for macro-influencers can be mitigated if their posts provide counterbalanced valence (both positive and negative assessments) or if they indicate an informative, rather than commercial, goal. These findings deepen understanding of how language arousal shapes consumer responses, reveal a psychological mechanism through which language arousal affects perceptions, and provide actionable insights for crafting more effective social media content.